Development and testing of a videogame intervention for symptom management among 8–18 years old children with cancer: a study protocol - Rubina Barolia; Zehra Fadoo; Sehrish Sajjad; Raisa B Gul; Saleem Sayani; Ahmed N Abbasi (BMJ Paediatrics Open)
Introduction Evidence shows that cancer treatment-related symptoms could be managed effectively in 8–18 years old children through Digital Health Interventions (DHIs), consequently improving their health-related quality of life (HRQOL). However, limited research is available about digitally mediated educative health interventions for children with cancer from lower-middle income countries like Pakistan. This study aims to develop a videogame intervention for children with cancer and test the clinical efficacy of the videogame concerning HRQOL and cancer treatment-related symptoms. Moreover, the following feasibility outcomes will be recorded: acceptability, appropriateness, cost, feasibility and intervention fidelity.Methods and analysis An exploratory sequential mixed methods design is used in this study. In the first phase of the study, we interviewed 28 participants (14 child–parent dyads) and assessed their symptom experiences affecting children’s HRQOL. Moreover, their preferences for the development of the videogame were also elicited. Based on the findings from relevant literature and the interviews, we developed the videogame in collaboration with clinical and digital experts in the study’s second phase. In the third phase of the study, a pilot randomised controlled trial will be conducted at a Tertiary Care Hospital in Karachi, Pakistan. There will be two groups: the intervention group and the control group. The intervention group children will receive the videogame application for 8 weeks, during which symptom management strategies will be taught to them. Children in the attention control group will receive weekly WhatsApp messages on healthy behaviours.The primary outcome will be the HRQOL of children, and the secondary outcome will be cancer symptoms frequency and distress. These outcomes will be assessed preintervention and 8 weeks post intervention. The feasibility outcomes will be assessed quantitatively and qualitatively through a questionnaire, videogame dashboard, interviews with a subset of intervention group child–parent dyads and a focus group discussion with nurses and doctors, post intervention, respectively.Ethics and dissemination The study has been approved by the Ethics Review Committee of the Aga Khan University (2022-6833-21251). Data are accessible only to the research team in a secure form. The findings will be disseminated through publications.Trial registration number ClinicalTrials.gov Identifier NCT05796895, registered in April 2023.